Infective endocarditis causing mitral valve stenosis – a rare but deadly complication: a case report. (December 2017) - Hart, Michael; Shroff, Gautam
Abstract Background Infective endocarditis rarely causes mitral valve stenosis. When present, it has the potential to cause severe hemodynamic decompensation and death. There are only 15 reported cases in the literature of mitral prosthetic valve bacterial endocarditis causing stenosis by obstruction. This case is even more unusual due to the mechanism by which functional mitral stenosis occurred. Case presentation We report a case of a 23-year-old white woman with a history of intravenous drug abuse who presented with acute heart failure. Transthoracic echocardiography failed to show valvular vegetation, but high clinical suspicion led to transesophageal imaging that demonstrated infiltrative prosthetic valve endocarditis causing severe mitral stenosis. Despite extensive efforts from a multidisciplinary team, she died as a result of her critical illness. Conclusions The discussion of this case highlights endocarditis physiology, the notable absence of stenosis in modified Duke criteria, and the utility of transesophageal echocardiography in clinching a diagnosis. It advances our knowledge of how endocarditis manifests, and serves as a valuable lesson for clinicians treating similar patients who present with stenosis but no regurgitation on transthoracic imaging, as a decision to forego a transesophageal echocardiography could cause this serious complication of endocarditis to be missed.